Advanced Custom Interconnects: A Paradigm Shift in High-Performance Computing Data Transfer Efficiency - FNU Parshant (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Recent advancements in high-performance computing (HPC) systems have highlighted the critical role of custom interconnects in achieving optimal system performance and efficiency. This article comprehensively analyzes modern custom interconnect architectures, focusing on their capacity to enhance data transfer speeds while maintaining power efficiency. The article examines the integration mechanisms for heterogeneous computing elements, including CPUs, GPUs, and specialized accelerators, and evaluates their impact on system-wide performance. The article explores advanced routing algorithms and coherence protocols that enable seamless communication across multiple processing elements while ensuring data consistency. The findings demonstrate that custom interconnects significantly improve system throughput and reduce latency in large-scale HPC deployments. Furthermore, the article analyzes the implications of these advancements for cloud computing, artificial intelligence, and big data analytics applications. This article contributes to the understanding of next-generation computing infrastructure by highlighting the crucial relationship between interconnect design and overall system performance while addressing the escalating demands of modern computational workloads.